CLINICAL EVALUATION OF EFFECTS OF LOW-LEVEL LASERS ON PAIN DURING CAVITY PREPARATION - Kaur, Maj Summerdeep; Sharma, Lt Col Sonali; Awasthi, Maj Pankaj (International Journal of Research -GRANTHAALAYAH, 2018)
Aim: To study the effects of low level laser on pain during cavity preparation. Background: Laser irradiation stabilizes the nerve membrane through an increase in adenosine triphosphate (ATP) production and enhanced redox system of the cell. Dental pulp is innervated by non- myelinated C fibres. Laser irradiation reduces the conduction of Ad and C fibres (small diameter fibres), both of which transmit nociceptive pain. The stabilization of the nerve membrane increases neural latency and decreases pain transmission. This study explores whether pre-irradiation with laser reduces pain perception during cavity preparation. Methodology: A clinical study was done on 50 patients reporting to Army Dental Centre(R&R) having moderate and deep size carious lesions on first/second premolar’s bilaterally. The patients selected was apprehensive. On one side, low level lasers irradiation was done prior cavity preparation (Test). On the other contralateral tooth type cavity preparation was done without local anesthesia (Control). The patients pain threshold was noted for both control and test groups using Visual Analogue Scale (VAS). The data was computed and statiscally analyzed. Results: The patients exhibited reduce pain perception in tooth which had prior laser irradiation as compared to the control group. Conclusion: Laser analgesia with low level lasers can be used as routine protocol for reducing pain perception in apprehensive patients undergoing cavity preparation.